Determination of polycyclic aromatic hydrocarbon content in heat-treated meat retailed in Egypt: Health risk assessment, benzo[a]pyrene induced mutagenicity and oxidative stress in human colon (CaCo-2) cells and protection using rosmarinic and ascorbic acids. (30th August 2019) - Darwish, Wageh Sobhy; Chiba, Hitoshi; El-Ghareeb, Waleed Rizk; Elhelaly, Abdelazim Elsayed; Hui, Shu-Ping
Highlights: High levels of PAHs were detected in heat-treated meats in Egypt. B[ a ]P induced mutagenicity and oxidative stress in colon cells at food-relevant doses. B[ a ]P induced alterations in mRNA expressions of xenobiotic metabolizing enzymes. Rosmarinic and ascorbic acids protected colon cells from B[ a ]P-adverse effects. Consumption of such molecules is advisable at high levels of exposure to B[ a ]P. Abstract: This study was undertaken to estimate the concentrations of the formed polycyclic aromatic hydrocarbons (PAHs) in heat-treated (boiled, pan-fried and grilled) meats collected from Egypt. Dietary intakes and cancer risks of PAHs among Egyptian adults were calculated. Benzo[ a ]pyrene (B[ a ]P)-induced mutagenicity and oxidative stress in human colon (CaCo-2) cell line and mechanisms behind such effects were also investigated. Finally, protection trials using rosmarinic (RMA) and ascorbic acids (ASA) were carried out. The results indicated formation of PAHs at high levels in the heat-treated meats. Calculated incremental life time cancer risk among Egyptian adults were 7.05179E−07, 7.00604 E−06 and 1.86069 E−05 due to ingestion of boiled, pan-fried and grilled meats, respectively. B[ a ]P-exposed CaCo-2 cells had high abilities for mutagenicity (490.05 ± 21.37 His + revertants) and production of reactive oxygen species. RMA and ASA protected CaCo-2 cells via reduction of B[ a ]P-induced mutagenicity and oxidative stress and upregulation of phase II detoxification enzymes and xenobiotic transporters.